Action Research In Education: A Way Towards Professional Development And Autonomy - Arias, Clara Inés; Restrepo, María Isabel (Íkala, Revista de Lenguaje y Cultura, 2009)
In this piece of writing we demonstrate the way the work dynamics of our team of teacher and student researchers (PEALE, acronym in Spanish) has contributed to our professional development and autonomy. We do not show the results of the action research project on evaluation of foreign language acquisition, but how it has promoted knowledge, experience, social, research, and evaluation skills, and attitudes towards evaluation and research. With examples of practices held in the team, we illustrate how reflexivity, dialectic critique, and collaboration, action research principles, are put into action. We also refer to the relationship among these principles and professional development, autonomy, and the researchers’ willingness to use the empowerment gained in the transformation of their educational communities. Received: 16-02-09 / Accepté: 02-06-09 How to reference this article: Arias, C. I. & Restrepo, M. I. (2009). Action Research in Education: A Way Towards Professional Development And Autonomy. Íkala. 14(2), pp.109-122.